A parenting programme to prevent abuse of adolescents in South Africa: study protocol for a randomized controlled trial - Cluver, L; Meinck, F; Shenderovich, Y; Ward, C; Herrero Romero, R; Lombard, C; Doubt, J; Steinert, J; Catanho, R; Wittesaele, C; DeStone, S; Salah, N; et al. (BioMed Central, 2016)
Background An estimated one billion children experience child abuse each year, with highest rates in low and middle income countries. The Sinovuyo Teen programme is part of Parenting for Lifelong Health, a WHO/UNICEF initiative to develop and test violence prevention programmes for implementation in low-resource contexts. The objectives of this parenting support programme are to prevent the abuse of adolescents, improve parenting, and reduce adolescent behavior problems. This trial aims to evaluate the effectiveness of Sinovuyo Teen compared to an attention-control group of a water hygiene programme. Methods This is a pragmatic cluster randomized controlled trial, with stratified randomization of 37 settlements (rural and peri-urban) with 40 study clusters in the Eastern Cape of South Africa. Settlements receive either a 14-session parenting support programme or a 1-day water hygiene programme. The primary outcomes are child abuse and parenting practices, and secondary outcomes include adolescent behavior problems, mental health and social support. Concurrent process evaluation and qualitative research are conducted. Outcomes are reported by both primary caregivers and adolescents. Brief follow-up measures are collected immediately after the intervention, and full follow-up measures collected at 3-8 months post-intervention. A 15-24 month follow-up is planned, but this will depend on financial and practical feasibility given delays related to high levels of ongoing civil and political violence in research sites. Discussion This is the first known trial of a parenting programme to prevent abuse of adolescents in a low or middle income country. The study will also examine potential mediating pathways and moderating factors.